Analisis Sistem dan Prosedur Persediaan Barang Dagang pada AndesMart Muara Tembesi - Fauziah Fauziah (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2021)
This study aims to determine whether the implementation of inventory system and inventory system applied in AndesMart is in accordance with the objectives of internal control. To obtain the necessary data then the authors use data collection tools in the form of interviews and literature. Data analysis method used is descriptive qualitative. From the results of the research, it can be concluded that the existing system at AndesMart Light is adequate in accordance with the objectives of internal control that there are elements of internal inventory control merchandise and the management of inventory merchandise procedures are running effectively.